KEWENANGAN KEPALA DESA DALAM MENYELESAIKAN SENGKETA MASYARAKAT BERDASARKAN UNDANG-UNDANG DESA - Romli, Desmawaty; Junaidi, Junaidi; Merta, Martindo (Solusi, 2022)
Public activities are never separated from social communication. Village community groups adhere to the characteristics of a peaceful and serene life, it cannot be separated from differences of opinion. Conflict issues that arise are triggered by conflicts of interest that cause debate. If this is allowed, it will damage the value of decency, social values ​​that cause disturbances in the security and comfort of the village community. The application of dispute resolution or violence in Indonesia, culturally, uses a lot of local community structures. To maintain harmony, organize and improve life in the village, it is more important to prioritize solving problems by consensus around people where there is a conflict, it is carried out peacefully. Ending the problem that was carried out by deliberation and consensus was carried out to maintain a harmonious life as the duty of the Village Head to resolve conflicts among its citizens. The authority of the Village Head to be able to resolve customary cases in examining and adjudicating according to their customs and not by law. The village head's obligation does not cancel the wishes of several individuals if they wish to have their case resolved in court, where it has been determined that the village head's obligations are to carry out his duties in resolving every community conflict in his village. The role of the Village Head as a conflict resolution issuer is very much needed to create a working judiciary in Indonesia. Conflict resolution based on local wisdom as explained in the Town Law can be utilized as much as possible in an effort to realize justice for the community.